Nasal mucosa inflammation induced by inhalation of methyl methacrylate acrylic prostheses: In Vivo study - Afriza, Dhona; Tofrizal, Alimuddin; Azzahra, Hana (Brazilian Dental Science, 2025)
Objective: The aim of this study was to determine, through histological analysis, the inflammatory effects of inhalation exposure to MMA on the nasal mucosa of mice. Material and Methods: This study involved an in vivo experiment using fifteen white mice (Mus musculus), which were randomly assigned to three groups. Group 1 served as the negative control, Group 2 was exposed to MMA for one week, and Group 3 was exposed to MMA for three weeks. Mice were exposed to MMA via inhalation for one and three weeks, six hours every day, five days a week. A semi-quantitative scoring system was used to evaluate the histology of the nasal mucosa, and the thickness of the nasal mucosa was also measured. The evaluation was conducted in five different fields of view, and the average score was documented. Data were analyzed statistically. The Shapiro–Wilk test was used to assess normality. Depending on distribution, group comparisons were performed using one-way ANOVA followed by LSD post hoc test or Kruskal–Wallis followed by Mann–Whitney post hoc test. A p-value <0.05 was considered statistically significant. Results: Group 1’s mucosal histology evaluation was within normal bounds. Group 2 showed nasal mucosa with mild histological damage. Group 3 showed nasal mucosa with moderate histological damage. Measurement of the thickness of the nasal mucosa of mice exposed to MMA showed an increase in mucosal thickness in both groups 2 and 3. In group 3, the thickness of the nasal mucosa increased more significantly. There was a significant difference between the three groups. Conclusion: Inhalation exposure to MMA leads to nasal mucosal inflammation that correlates with the duration of exposure, with mild inflammation observed after one week of exposure and moderate inflammation after three weeks. KEYWORDS Histology; Inhalation; Methyl methacrylate; Nasal mucosa; Toxicity.